Pancreatic Involvement in Pediatric Inflammatory Bowel Disease - Martín-de-Carpi, Javier; Moriczi, Melinda; Pujol-Muncunill, Gemma; Navas-López, Victor M. (Frontiers in Pediatrics, 2017)
Inflammatory bowel disease (IBD) is a chronic condition that includes 2 clinical entities: Crohn's disease (CD) and ulcerative colitis (UC). Although both entities mainly affect the gastrointestinal tract are considered multisystemic diseases and may present extraintestinal manifestations (EIM) involving other organs and systems. Pancreatic involvement in Pediatric IBD includes a heterogeneous group of clinical entities like acute pancreatitis, chronic pancreatitis, autoimmune pancreatitis, asymptomatic exocrine pancreatic insufficiency, increased pancreatic enzyme levels, structural abnormalities and granulomatous inflammation. Although the mechanism for pancreatic involvement in IBD is not clearly elucidated, is important to keep in mind the association of these two entities in order to perform a prompt diagnosis and establish an appropriate treatment. The objective of this review is to update the available evidence on pancreatic involvement in children with IBD.